GF-AAS Determination of Cadmium in DifferentCigarettes and Cigarette Smoke - Fatemi, S.J.; Sheikh, A.; Noroozian, E.; Afzali, D. (Asian Journal of Chemistry, 2010)
In the present work an electrothermal atomic absorption spectrometric method has been used for the determination of cadmium in cigarette constituents and smoke. The concentrations of cadmium in tobacco, tobacco ash and side-stream smoke were 1.3–3.1, 0.12–0.50 and 0.039–0.170 μg/g, respectively, for different cigarettes. Cadmium in the mainstream smoke was not detectable. It was, therefore, concluded that passive smokers are at a higher risk of intoxication by cadmium compared to smokers.